2010
DOI: 10.1186/1472-6963-10-273
|View full text |Cite
|
Sign up to set email alerts
|

Empirical studies on informal patient payments for health care services: a systematic and critical review of research methods and instruments

Abstract: BackgroundEmpirical evidence demonstrates that informal patient payments are an important feature of many health care systems. However, the study of these payments is a challenging task because of their potentially illegal and sensitive nature. The aim of this paper is to provide a systematic review and analysis of key methodological difficulties in measuring informal patient payments.MethodsThe systematic review was based on the following eligibility criteria: English language publications that reported on em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 30 publications
5
103
0
4
Order By: Relevance
“…We have explored the phenomenon in the context of Iran's health system by involving three main stakeholders. Previous studies have reported that people make informal payments to express gratitude (3,24,25), to get additional or better services (3,26), or because of cultural norms ingrained in their tradition, and weak laws (25). This study indicates that all of the above mentioned factors affect patients' decisions to make such payments, although some of them seem to play a more important role.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We have explored the phenomenon in the context of Iran's health system by involving three main stakeholders. Previous studies have reported that people make informal payments to express gratitude (3,24,25), to get additional or better services (3,26), or because of cultural norms ingrained in their tradition, and weak laws (25). This study indicates that all of the above mentioned factors affect patients' decisions to make such payments, although some of them seem to play a more important role.…”
Section: Discussionmentioning
confidence: 62%
“…Dabalen and Wane state that informal patient payments are a sensitive research topic due to their illegality in some countries. This implies that there may be difficulties in estimating their real scope and magnitude, and above all difficulties in determining the frequency of their occurrence (24).…”
Section: Limitationsmentioning
confidence: 99%
“…Így összevetve jelen eredményeinkkel, elmondható, hogy a két évvel korábbi felméréshez képest nőtt a családorvos-rezidensek körében a hálapénzt elutasítók aránya (50% vs. 38,3%) [27]. Vizsgálati eredményeinket árnyalja, hogy a "hálapénz-problémában" nem a családorvoslás a leginkább érintett ágazat: mind a nemzetközi, mind pedig a hazai vizsgála-tok kimutatták, hogy a fekvőbeteg-ellátás a legjobban érintett terület [4,5,[28][29][30], így eredményeink nem ál-talánosíthatóak más szakmákra, szakterületekre. A Markusovszky-ösztöndíj megléte is finomíthatja eredménye-inket: ezen ösztönző minden bizonnyal enyhíti a fiatal orvosgeneráció financiális nehézségeit, és elviekben szigorú tiltás alá vonja a hálapénz elfogadásának gyakorlatát.…”
Section: áBraunclassified
“…Elsősorban a posztszovjet országok sajátossága, de megjelenik az afrikai, a dél-amerikai és egyes ázsiai egészségügyi rendszerekben is, valamint ismert a fogalom Törökországban, Görögországban és Olaszországban [3][4][5][6][7]. A jelenség háttere, mozgatóru-gói, múltja, jelene és jövője számos szakterület tudományos diskurzusának kiemelt kérdése hazánkban is.…”
unclassified
“…Other studies in extending this definition define informal payments as cash or in-kind payments that may happen alongside formal official payment for health care services. 27,28 These payments when suspected to violate accountability mechanisms within the health system may create inefficiencies and inequity issues with the use of equal services by all patients. 27,29,30 …”
Section: Outcome Measuresmentioning
confidence: 99%